Control of Three-Axis Manipulator Placed on Heavy-Duty Pentapod Robot - Hulako, Halit; Yakut, Oguz (Elsevier, 2021)
Research on the effective use of joint-legged robots continues rapidly in many sectors. However, studies on pentapod robots are rare. In this study, a heavy-duty 5-legged robot on which a manipulator's arm with 3-axis and rotating joints is placed was modeled in a Matlab Simscape Multibody environment. The walking simulations of the robot and the position control of the manipulator arm were carried out. PID control method was used for the control of the joints. In order to minimize the vibrations of the base and the gripper end, a suitable gait sequence for 5 leg structure was formed. The effects of vibrations in the robot's base during the walk on manipulator position control are presented graphically and the results are discussed.
Keywords: Pentapod Robot; Simscape Multibody Model; Gait; PID Control; 3-axis manipulator